THE INTRICACIES OF IRONY: TYPES AND EXAMPLES (Scientific journal of the Fergana State University, 2024)
Various stylistic devices in literature are widely used in our everyday speech, and their analysis forms a positive skill for understanding. One of the most common of such methodological tools is irony. In the study of irony at the scientific level, the scientific researches of foreign scientists, as well as Uzbek scientists, are comprehensive from a theoretical and practical point of view. In this article, attention is paid to different forms of irony, and in the process of analysis, in addition to three types of irony (dramatic, verbal, situational irony), cosmic and romantic types are also analyzed by means of examples.